PENGARUH INVESTASI, PENGELUARAN PEMERINTAH DAN TENAGA KERJA TERHADAP PDRB KABUPATEN/KOTA DI PROPINSI BANTEN TAHUN 2010-2014 - Ahmad Jazuli Rahman; Aris Soelistyo; Syamsul Hadi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
The purpose of the study was to determine the effect of variable investment (domestic and foreign), Government Expenditure, Labor (Labor Force Works) for the Gross Regional Domestic Product in Banten Province. The analysis tool used regression panel data. the test results obtained deteminasi coefficient R ^ 2 for the fixed effect model of 0.9987. This showed that the ability of independent variables in explaining the dependent variable of 99.87%. The results of the research study concluded that Investment, Government Expenditures and Labor was positive and significant impact on the Gross Regional Domestic Product with the results of Statistics 3.55 F more large than F table is 2.38. While the partial test results showed that investment and government expenditure was a significant and positive effect while the labor was negative effect on the Gross Regional Domestic Product.